1999
DOI: 10.1002/cjce.5450770405
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of double‐to‐single‐loop transition in stirred vessels

Abstract: The velocity characteristics of the flows in a fully baffled vessel of diameter T = 290 mm stirred by a Rushton impeller of' diameter D = TI3 were investigated by means of laser-Doppler anemometry measurements. The effects of clearance and rotational speed on the flow patterns in the vessel were studied. It was found that at impeller clearances from the bottom of the vessel (C) around 0.2 Tthe characteristic double-loop flow pattern undergoes a transition to a single-loop one with the impeller stream direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 18 publications
8
48
0
Order By: Relevance
“…They used two impeller off-bottom clearances, C = T/3 and C = T/2, observing a secondary circulation loop with the higher clearance. Montante et al (1999) provided a detailed investigation of the flow field generated by D = T/3 RT placed at different off-bottom clearances varying from C = 0.12T to C = 0.33T. They found that the conventional radial flow pattern (termed "double-loop" pattern) occurred for C = 0.20T, but it was replaced by an axial flow pattern (termed "single loop" pattern) as the clearance was decreased to C = 0.15T.…”
Section: Classification Of Flow Instabilitiesmentioning
confidence: 99%
“…They used two impeller off-bottom clearances, C = T/3 and C = T/2, observing a secondary circulation loop with the higher clearance. Montante et al (1999) provided a detailed investigation of the flow field generated by D = T/3 RT placed at different off-bottom clearances varying from C = 0.12T to C = 0.33T. They found that the conventional radial flow pattern (termed "double-loop" pattern) occurred for C = 0.20T, but it was replaced by an axial flow pattern (termed "single loop" pattern) as the clearance was decreased to C = 0.15T.…”
Section: Classification Of Flow Instabilitiesmentioning
confidence: 99%
“…A standard six bladed Rushton turbine was used in the suspension experiments. A close off-bottom impeller clearance was chosen in order to ensure a "single-loop" flow configuration [12]. The agitator speed here investigated (380 rpm) was sufficient to get fully suspended conditions at steady state.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…Impeller off-bottom clearance is an important geometric parameter and its effect on flow patterns and power consumption in batch stirred tanks has been a subject of several experimental and computational investigations (Nienow, 1968;Conti et al, 1981;Ibrahim and Nienow, 1995;Armenante and Nagamire, 1998;Montante et al, 1999Montante et al, , 2001a. The most important finding of these studies is that below a certain value of clearance even a radial flow impeller behaves like an axial flow impeller.…”
Section: Introductionmentioning
confidence: 99%